2022
DOI: 10.21037/apm-22-528
|View full text |Cite
|
Sign up to set email alerts
|

Illness uncertainty and its associated factors in coronary heart disease patients with heart stent implantation: a cross-sectional study

Abstract: Background: The purpose of this study was to investigate the illness uncertainty and its influencing factors in patients after heart stent implantation, and to explore the relationship between uncertainty of disease, selfmanagement behavior of coronary heart disease and quality of life after stenting. Methods:A cross-sectional study of 168 patients with cardiac stent implantation on illness uncertainty in a tertiary hospital in Shanghai. The General Information Questionnaire and the Mishel's Uncertainty in Ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This indicated that specialized nursing outpatient case management can effectively alleviate patients' adverse emotions. The reason behind this may be attributed to the detailed information collection and assessment of each patient, the development of personalized care plans tailored to individual needs and circumstances, and the better fulfillment of patients' psychological and emotional needs, thus alleviating adverse emotions[ 23 - 25 ]. Additionally, specialized nursing outpatient nurses help patients better understand and cope with postoperative emotional changes by providing relevant health education and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that specialized nursing outpatient case management can effectively alleviate patients' adverse emotions. The reason behind this may be attributed to the detailed information collection and assessment of each patient, the development of personalized care plans tailored to individual needs and circumstances, and the better fulfillment of patients' psychological and emotional needs, thus alleviating adverse emotions[ 23 - 25 ]. Additionally, specialized nursing outpatient nurses help patients better understand and cope with postoperative emotional changes by providing relevant health education and psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…When patients and their families cannot understand the information provided by ICU physicians or get less information, their uncertainty would increase, which would further cause them anxiety. Research showed that uncertainty accounted for 30.2% of the factors that cause family members’ transfer anxiety, and providing information was a key factor in reducing uncertainty and anxiety [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…When patients and their families could not understand the information provided from ICU physicians or get less information, their uncertainty would increase, which would further cause them anxiety. Researches showed that the uncertainty accounted for 30.2% of the factors that cause family members' transfer anxiety, and providing information was a key factor in reducing uncertainty and anxiety [38,39]. Preoperative education was also helpful to improve the prognosis of patients undergoing cardiac surgery [31] because it may enhance patients' knowledge; besides, meeting their information needs could also mitigate their distress [40].…”
Section: Summary Of Main Ndingsmentioning
confidence: 99%